Mammary-specific expression of Trim24 establishes a mouse model of human metaplastic breast cancer - Vrutant V. Shah (Nature Portfolio, 2021)
Human metaplastic breast cancers (MpBC) are a rare, aggressive subclass of triple-negative breast cancers. Here, the authors show over-expression of histone reader TRIM24 is sufficient to generate tumors with a molecular signature of metabolic dysfunction and EMT in a mouse model of human MpBC.